Taoren Honghua Drug Attenuates Atherosclerosis and Plays an Anti-Inflammatory Role in ApoE Knock-Out Mice and RAW264.7 Cells - Wang, Yiru; Jia, Qingyun; Zhang, Yifan; Wei, Jing; Liu, Ping (Frontiers in Pharmacology, 2020)
Taoren Honghua Drug (THD) is a traditional Chinese medicinal drug that has been used to treat cardiovascular disease for a long time. The Aim of the study is to investigate the effects of THD on inflammation and atherosclerosis in apolipoprotein E knock-out (ApoE-/-) mice and RAW264.7 cells. ApoE-/- mice fed with high fat diet (HFD) for eight weeks were randomly divided into four groups and then fed with HFD, or HFD plus THD at concentrations of 3.63g/ml, 1.815g/ml and 0.9075g/ml. Additionally, RAW 264.7 cells were intervened with lipopolysaccharide or lipopolysaccharide plus different concentrations of THD. In ApoE-/- mice fed with THD, body weight (P< 0.001), triglyceride (P< 0.05, P< 0.01), total cholesterol (P< 0.05), IL-6 and TNF- levels (P< 0.01) of serum were decreased, but IL-10 level was increased (P<0.05). Compared to mice without THD, smaller plaque sizes (P< 0.001), less lymph vessel contents (P< 0.001), and lower T cell contents in lymph nodes were also found in ApoE-/- mice fed with THD. In RAW264.7 cells, groups with LPS plus THD had lower IL-6 and TNF-, and higher IL-10 than LPS group, as revealed by ELISA kits. Gene expression of these three cytokines were consistent with the ELISA results (P< 0.001). In addition, a decrease of total or phosphorylated ERK1/2, JNK, p38, ERK5, STAT3 and AKT were detected, so was the translocation of NF-B p65 from nuclear to cytoplasm. These results suggested that THD could attenuate atherosclerosis and play an anti-inflammatory role via MAPKs, ERK5/ STAT3 and AKT/ NF-B p65 signaling pathways in ApoE-/- mice and lipopolysaccharide-induced RAW264.7 cells.